Digital strategic planning tools and their impact on achieving organizational success/A survey study of the opinions of a sample of administrative leaders and employees in the Ministry of Health/Abu Ghraib General Hospital Directorate - Muayad AbdulKareem shakir Al-Naqib,; Basem Faisal Abd Nayef, (Technium Business and Management, 2025)
This research aims to study the impact of using digital strategic planning tools on achieving organizational success. The practical aspect of this study was implemented in the field at the Ministry of Health, Abu Ghraib General Hospital Directorate. The questionnaire was distributed to a sample of (30) employees at the Ministry of Health, Abu Ghraib General Hospital Directorate. The study examined the impact of digital strategic planning tools (such as SWOT analysis, PEST analysis, and value chain analysis) on organizational success through several organizational dimensions, such as resources, organizational structure, and management. The analysis began with a descriptive study of the sample's demographic characteristics, which revealed diversity in gender, age, educational attainment, and years of service, reflecting a realistic representation of the nature of the university's workforce. The internal consistency of the research tool was then analyzed using Cronbach's alpha test, with a reliability coefficient of (0.75), indicating that the questionnaire has a high degree of reliability. A descriptive analysis of the digital strategic planning tools was then conducted. The results showed that the arithmetic averages for all tools were within good levels, indicating their actual, albeit imperfect, application. The strengths of the SWOT analysis were the most evident and utilized, while external opportunities were less emphasized. The PEST analysis results also showed that political and technological factors were considered to a greater extent than social and cultural factors. The value chain analysis recorded good levels of application, particularly regarding identifying activities that directly add value to the customer. Regarding organizational success, the results showed variations in the evaluation of human, financial, and technical resources, highlighting the need to develop human resources and provide more modern equipment. The organizational structure also demonstrated good organizational standards, with some challenges in delegating authority. The management dimension yielded average results, with clear variations in participants' opinions regarding management efficiency and its alignment with labor market requirements. Statistical hypotheses were tested using Pearson's correlation coefficient and linear regression to determine the relationship between digital strategic planning tools and organizational success. The results revealed a significant positive correlation and influence between the two variables.